(untitled) (Jurnal Kemanusiaan, 2017)
The purpose of this paper is to empirically a model that reflects the different types of benefit perceived by unit trust retail investors. A quantitative analysis through a personal survey to unit trust customers was performed. A customer study in the mutual fund service industry was conducted on one of the famous government linked company that provides unit trust products in Malaysia. Data were analyzed through factor analysis and regression model is estimated. The results from the regression model suggest that functional and experiential benefits have a major influence on customer satisfaction and purchase intentions. The findings also suggest that unit trust providers should consider treating consumers as partners in their provision of existing services toward unseen criteria and overlooking these less visible area, such as feelings of being successful, comfortable, confidence, independent, and having optional to make decision. This study is strategically important to unit trust providers in Malaysia to encourage them to offer new benefit for their customer. The present study is limited in its scope and a first approach of benefit construct is considered and future research was suggested by adding new constructs in order to deepen into the analysis of the relationship between customer and unit trust providers.